Pengaruh Kurs Tukar, Dana Asing, dan Volume Perdagangan Terhadap Indeks Harga Saham - Tuti Fitriani; Said Kelana Asnawi; Hendrian Hendrian (Politeknik Ganesha Medan, 2022)
Fluctuations in the stock price index indicate a market mechanism: the interaction between supply and demand for traded shares. Several factors can influence the movement of the stock price index, including the exchange rate, foreign funds, and trading volume. This study aims to analyze the effect of the exchange rate, foreign funds, and trading volume on the composite stock price index during the 2018-2020 time period, which is calculated weekly, where data on Wednesdays represent weekly data for each variable, so the data in this study amounted to 154 data. This research analysis method uses multiple linear regression with an ordinary least square approach. The results showed that the exchange rate depreciation would significantly reduce the joint-stock price index, while foreign funds and trading volume did not significantly affect the movement of the joint-stock price index in the Indonesia Stock Exchange